A space-frequency multiplicative regularization for force reconstruction problems. (1st May 2018) - Aucejo, M.; De Smet, O.
Highlights: A space-frequency regularization for force reconstruction problems is presented. A unique framework to deal with both localization and spectral reconstruction problems. The pertinence of the method is evaluated from numerical and experimental validations. The proposed approach performs generally better than or similarly to standard approaches. Abstract: Dynamic forces reconstruction from vibration data is an ill-posed inverse problem. A standard approach to stabilize the reconstruction consists in using some prior information on the quantities to identify. This is generally done by including in the formulation of the inverse problem a regularization term as an additive or a multiplicative constraint. In the present article, a space-frequency multiplicative regularization is developed to identify mechanical forces acting on a structure. The proposed regularization strategy takes advantage of one's prior knowledge of the nature and the location of excitation sources, as well as that of their spectral contents. Furthermore, it has the merit to be free from the preliminary definition of any regularization parameter. The validity of the proposed regularization procedure is assessed numerically and experimentally. It is more particularly pointed out that properly exploiting the space-frequency characteristics of the excitation field to identify can improve the quality of the force reconstruction.